Fatigue damage mechanism of railway wheels under lateral forces. (November 2015) - Zhou, Guiyuan; He, Chenggang; Wen, Guang; Liu, Qiyue
Abstract: Under conditions of curve negotiating and hunting, lateral force is generated at the wheel/rail interface that can damage the wheel tread. The rolling contact tests were performed on a JD-1 wheel/rail simulation apparatus with different lateral forces between the rail and wheel rollers. The results indicate that plastic deformation and mild wear dominated at each side of the contact area, while fatigue damage dominated at the middle region. Drastic changes in stress and stress direction from the high stress region to the lower stress region can lead to plastic accumulation and the initiation of fatigue cracks. The formation and breaking of metal tongue make big contribution to material loss in this condition. Highlights: This paper deals with the damage mechanisms of wheel steel under lateral forces. Plastic deformation, mild wear and fatigue dominated at different regions. Material flow due to lateral force is the latent cause of diversified damages. RCF cracks can initiate under metal tongue due to material accumulation. Formation and breaking of metal tongues make big contribution to material loss.